11. Visual electrophysiology revealed the diagnosis in an unusual case of bilateral blindness at the multiple sclerosis center. A case of bilateral chronic optic neuropathy related to inverted papilloma of paranasal sinuses. Issue 4 (April 2016) - Silipo, S.; Calabrese, M.; Juergenson, I.; Tozzi, Mc.; Monaco, S.; Bertolasi, L.
Abstract : The afferent visual pathway can be evaluated by the neurophysiologist using full-field ERG, transient or stationary P-ERG and pattern VEP. We report a case of a 65 year-old man which was admitted to the Multiple Sclerosis Center because of chronic bilateral blindness where the visual electrophysiology gave important clues for an unexpected diagnosis. Recurrent episodes of subacute vision loss, without improvement after steroid therapy, led the patient to blindness in the right eye at age 45. Ten years later he developed a progressive loss of visual acuity on the contralateral eye. Ophthalmological examinations disclosed also recurrent episodes of left anterior uveitis lately complicated by cataract. However the visual acuity on the left eye didn't improve after phacoemulsification. Brain and spinal MRI were normal as well as CSF examination and anti NMO antibodies. Rheumatological screening revealed only a positivity to HLA B27. The visual electrophysiology was consistent for bilateral chronic optic neuropathy without involvement of the retina or features of Leber disease or glaucoma. A tailored MRI of the orbits and CT scan of the face disclosed a butterfly-like inverted papilloma of paranasal sinuses which destroyed the wall of both optic canals. The patient underwent surgical treatment.